2015
DOI: 10.1002/2014gl062937
|View full text |Cite
|
Sign up to set email alerts
|

Global monthly sea surface nitrate fields estimated from remotely sensed sea surface temperature, chlorophyll, and modeled mixed layer depth

Abstract: Information about oceanic nitrate is crucial for making inferences about marine biological production and the efficiency of the biological carbon pump. While there are no optical properties that allow direct estimation of inorganic nitrogen, its correlation with other biogeochemical variables may permit its inference from satellite data. Here we report a new method for estimating monthly mean surface nitrate concentrations employing local multiple linear regressions on a global 1° by 1° resolution grid, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We use monthly satellite‐based data to define temperature (sea surface temperature (SST)), light, and nitrate for the surface mixed layer [ Arteaga et al , ]. Light is represented by the median mixed layer light level ( I g ), which approximates the average light intensity experienced by phytoplankton cells in the surface mixed layer ( I g ) [ Behrenfeld et al , ], Ig=1D·PAR·eK490·MLD2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use monthly satellite‐based data to define temperature (sea surface temperature (SST)), light, and nitrate for the surface mixed layer [ Arteaga et al , ]. Light is represented by the median mixed layer light level ( I g ), which approximates the average light intensity experienced by phytoplankton cells in the surface mixed layer ( I g ) [ Behrenfeld et al , ], Ig=1D·PAR·eK490·MLD2 …”
Section: Methodsmentioning
confidence: 99%
“…The use of different modeled MLD outputs is intended to cover the whole study period (2005–2010) with the most recent available model (i.e., MLD output is not available from HYCOM before October 2008 and FNMOC‐HIRES before July 2005). Monthly global surface nitrate concentrations are taken from the data set produced by Arteaga et al []. These global nitrate fields are obtained from multiple local linear regressions of satellite‐derived SST, Chl, and model‐based MLD.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this study, there were two main methods for estimating the concentrations of nutrients. Firstly, global-or basin-scale models were employed based on the relationship between nutrients, sea surface temperature (SST), and chlorophyll concentration [34][35][36]. However, such models are not applicable to coastal waters, because there is little change in environmental elements, such as SST, on a small spatial scale.…”
Section: Comparison With Spectrum-based Algorithmsmentioning
confidence: 99%
“…To ensure that the chosen number of clusters, k, is representative of the system, typically one needs to repeat the technique for various values of k, and, using visual inspection, select the optimal value for k when the resulting clusters become repetitive or contain no additional information. Objective methods have been proposed (e.g., Bankert and Solbrig, 2015), where the average radius of each cluster (the distance from the centroid to the most distant member within a cluster) is computed for decreasing k. Bankert and Solbrig (2015) found that when the number of clusters falls below the optimal k, the average radius grows rapidly. We employ a similar methodology here.…”
Section: Sensitivity To Predefined Number Of Clustersmentioning
confidence: 99%
“…For example, this technique has been used to define atmospheric weather states by identifying cloud regimes (Jakob and Tselioudis, 2003;Rossow et al, 2005;Williams and Webb, 2009;Tselioudis et al, 2013;Bodas-Salcedo et al, 2014;Oreopoulos et al, 2016). Bankert and Solbrig (2015) were able to extract a 3-D cloud representation using cluster analysis. This technique has also been used to characterize water types in lakes (Trochta et al, 2015), hydraulic habitat composition in rivers (Hugue et al, 2016), phenology patterns in forests (Trans Mills et al, 2011), solar variability (Zagouras et al, 2013), ENSO phenomena (Radebach et al, 2013), and regions with characteristic hydrological responses (Halverson and Fleming, 2015), among many other applications.…”
Section: Introductionmentioning
confidence: 99%